Effects of Different Cultivation Substrates on the Growth of Podocarpus macrophyllus and the Rhizosphere Soil Microbial Community Structure - Xiaomin Liang; Donghua Zhong; Congyu Zhang; Yongfang Pan; Chenning Zhang; Herong Guo; Xiaoling Zhu; Xiaocong Li; Yuxuan He; Shaopeng Huang; Jincai Tu; Ting Gao; et al. (Agronomy)
Podocarpus macrophyllus is an evergreen tree with significant ornamental, economic, and medicinal value, widely used in landscape gardening and bonsai production. However, systematic research on the optimal substrate ratios required for its efficient cultivation remains relatively scarce. This study compared the effects of two cultivation substrates (SJ1: 80% native soil + 20% fine sand and SX2: 25% native soil + 25% coarse sand + 25% peat soil + 25% coconut coir) on the growth of P. macrophyllus. Soil physicochemical properties and plant physiological and biochemical indices were measured, and the rhizosphere microbial community structure was analyzed using Illumina MiSeq high-throughput sequencing. The results show that P. macrophyllus grown in the SX2 substrate exhibited significantly greater ground diameter, plant height, chlorophyll content, and soluble protein content than those in the SJ1 substrate. Microbial community analysis indicates that the two different substrates had little impact on alpha diversity. In the bacterial community, the dominant phylum in the SJ1 substrate was Acidobacteriota, whereas in the SX2 substrate, it was Pseudomonadota. In the fungal community, Ascomycota was the dominant phylum in both SJ1 and SX2. Redundancy analysis (RDA) reveals that water content and total porosity were the primary factors influencing the bacterial community structure. Based on physiological indicators and microbial community composition, the SX2 substrate was more conducive to the growth of P. macrophyllus in terms of plant height and ground diameter. Therefore, this study provides valuable insights for substrate selection and optimization in the cultivation of P. macrophyllus.